Is COVID‐19 infection more severe in kidney transplant recipients?. Issue 3 (28th January 2021) - Caillard, Sophie; Chavarot, Nathalie; Francois, Hélène; Matignon, Marie; Greze, Clarisse; Kamar, Nassim; Gatault, Philippe; Thaunat, Olivier; Legris, Tristan; Frimat, Luc; Westeel, Pierre F.; Goutaudier, Valentin; et al.
Abstract : There are no studies which have compared the risk of severe COVID‐19 and related mortality between transplant recipients and nontransplant patients. We enrolled two groups of patients hospitalized for COVID‐19, that is, kidney transplant recipients (KTR) from the French Registry of Solid Organ Transplant ( n  = 306) and a single‐center cohort of nontransplant patients ( n  = 795). An analysis was performed among subgroups matched for age and risk factors for severe COVID‐19 or mortality. Severe COVID‐19 was defined as admission (or transfer) to an intensive care unit, need for mechanical ventilation, or death. Transplant recipients were younger and had more comorbidities compared to nontransplant patients. They presented with higher creatinine levels and developed more episodes of acute kidney injury. After matching, the 30‐day cumulative incidence of severe COVID‐19 did not differ between KTR and nontransplant patients; however, 30‐day COVID‐19‐related mortality was significantly higher in KTR (17.9% vs 11.4%, respectively, p  = .038). Age >60 years, cardiovascular disease, dyspnea, fever, lymphopenia, and C‐reactive protein (CRP) were associated with severe COVID‐19 in univariate analysis, whereas transplant status and serum creatinine levels were not. Age >60 years, hypertension, cardiovascular disease, diabetes, CRP >60 mg/L, lymphopenia, kidney transplant status (HR = 1.55), and creatinine level >115 µmol/L (HR = 2.32) were associated with COVID‐19‐related mortality in univariate analysis. In multivariable analysis, cardiovascular disease, dyspnea, and fever were associated with severe disease, whereas age >60 years, cardiovascular disease, dyspnea, fever, and creatinine level>115 µmol/L retained their independent associations with mortality. KTR had a higher COVID‐19‐related mortality compared to nontransplant hospitalized patients. Abstract : The increased mortality risk observed for hospitalized kidney transplant recipients compared to matched nontransplant patients is primarily driven by altered kidney function.